Talulah's back in town : [large type] a novel - Novak, Brenda (Novak, Brenda. Coyote Canyon novel, 2023)
"Fourteen years after leaving her fiancé at the altar, Talulah Barclay returns to her hometown of Coyote Canyon, Montana, to settle her great-aunt's estate. As she'd feared, her runaway bride reputation is waiting right where she left it, and her ex's best friend, Brant, isn't about to let her slip by unnoticed. Brant has always been a loyal friend, but he remembers more about Talulah than he cares to admit. Talulah has no plans to stay in town after she fixes up her aunt's house, even if the sparks with Brant give her reason to linger. But a lot has changed since Talulah last turned tail--maybe her heart has changed, too?"--